Mempelajari Makna Teologis Sepuluh Perintah Allah Bagi Umat Kristen (Keluaran 20:1-17): Indonesia - Pasaribu, James; Garamba, Iswan (Journal of Education Research, 2024)
This research aims to decipher the meaning of the Ten Commandments of God and study them for today's life. The theological significance of each commandment is examined, and how these principles remain relevant to Christian life today. The method used is qualitative collected from literature searches. Directly related literature sources will be selected to answer research needs. The collected data are analyzed and studied with each other. This research finds that the Ten Commandments of God serve as an ancient moral guide and are relevant as a foundation for facing various modern ethical challenges. The Ten Commandments include directions regarding man's relationship with God (the first to fourth commandments) and man's relationship with others (the fifth to tenth commandments), which form the basis of Christian ethics. The researcher suggests that the Ten Commandments continue to be a living guide for Christian character in obedience, holiness, and commitment to carrying out God's will.